THE ROLE OF PHYSICS COURSES IN THE TRAINING OF FUTURE CIVIL ENGINEERS (American Journal of Research in Humanities and Social Sciences, 2023)
The article examines the role of the physics course in the training of future civil engineers studying in the field of architectural and construction education at technical universities, the conditions for training future civil engineers in the course of general physics, the tasks of teaching physics in technical universities, as well as the stages of ensuring interdisciplinary.